Peningkatan Pengetahuan Kesehatan Siswa/Siswi RA dan PAUD Abu Bakar As-Sidhiqqi tentang Manajemen Pembuangan Sampah Yang Baik - Ari Septianingtyas Purwandhini; Endang Wahyu Pudjiastutik; Deddy Kurniawan; Abdul Hadi (Jurnal Pengabdian Indonesia, 2024)
Waste is a problem that is still faced by most countries in the world. Currently, there are still many people who still throw household waste in rivers. Therefore, it is necessary to instill the intention from childhood that "I must throw away my rubbish in its proper place." As the next generation, children are at risk of experiencing disaster due to poor waste management. Because the earlier children are given knowledge, especially about good habits, the more likely they will continue to be. carried over into a habit until they grow up. To be able to provide early education and to provide good habits regarding waste disposal management, PAUD/RA located in urban areas are RA and PAUD Abu Bakar As-Sidhiqqi, Gebang Village, Patrang District. This was carried out as expected, namely high participation and high enthusiasm from the participants in the extension process. Then for sustainability, there was monitoring and coaching so that the results were more optimal and more motivated to continue and develop this program.